The carbon footprint of health care delivery in Western Australia's public health systemResearch in context - Amanda Irwin; Arunima Malik; Aditya Vyas; Catherine Bateman; Sarah Joyce (Elsevier, 2024)
Summary: Background: Health systems have a dual imperative to take action on climate change. First, they must develop climate resilient health services in response to the direct and indirect impacts of climate change on health. Second, they must reduce their own carbon footprint since health systems are a significant contributor to global greenhouse gas emissions. Methods: An environmentally-extended multi-region input-output analysis was carried out, incorporating National Accounts data for Australia and annual expenditure data from WA Health for financial year 2019-20. Expenditure data were categorised to one of 344 economic sectors and by location of the provider of goods or services purchased. Findings: WA Health contributes 8% of WA's total carbon footprint, driven by expenditure on chemicals (23.8% of total), transport (20.2% of total), and electricity supply (19.7% of total). These 3 sectors represent 63.7% of WA Health's carbon footprint, but only 10.8% of its total expenditure. Interpretation: Reducing emissions related to health service provision in WA will require a holistic approach that leverages carbon footprinting insights and integrates them into organisational decision-making across all health programs. The high carbon-intensity of the transport and chemicals sectors supports previous research calling for a reduction in unnecessary pathology testing and the transition to delivery of non-urgent health care via sustainable models of telehealth. The impact of WA's size and location presents challenges, with a predominantly non-renewable energy supply and reliance on transport and supply chains from other states adding significantly to emissions. Funding: The study received funding from the Australian Research Council, The University of Sydney, and the WA Department of Health. The full list of funding information can be found in Acknowledgements.